2018
DOI: 10.1371/journal.pone.0199132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose silver nanoparticle treatment on the structure and community composition of bacterial freshwater biofilms

Abstract: The application of engineered silver nanoparticles (AgNPs) in a considerable amount of registered commercial products inevitably will result in the continuous release of AgNPs into the natural aquatic environment. Therefore, native biofilms, as the prominent life form of microorganisms in almost all known ecosystems, will be subjected to AgNP exposure. Despite the exponentially growing research activities worldwide, it is still difficult to assess nanoparticle-mediated toxicity in natural environments. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…(2019) . Few studies, however, have investigated the subinhibitory effects of AgNPs on clinical isolates or environmental microorganisms ( Yang and Alvarez, 2015 ; Garuglieri et al., 2016 ; Grün et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) . Few studies, however, have investigated the subinhibitory effects of AgNPs on clinical isolates or environmental microorganisms ( Yang and Alvarez, 2015 ; Garuglieri et al., 2016 ; Grün et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… Garuglieri et al. (2016) showed that treatment with AgNPs sized 14 ± 0.3 nm increased motility and Grün et al. (2018) found that treatment with 30–70 nm AgNPs enhanced biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetrical porphyrins are employed since asymmetry is known to result in high singlet oxygen quantum yield in porphyrins ( Oliveira et al, 2009 ). In addition, AgNPs and DNDS used in this work are also known for their antimicrobial potency ( Szunerits et al, 2016 ; Grün et al, 2018 ). A metal free porphyrin have been linked to Ag NPs (Ag-S bond), for antimicrobial studies ( Elashnikov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, experiments conducted in more complex environments to determine if current levels of exposure to NPs are endangering microorganisms or microbial processes are more equivocal. Ag-NPs appear to have limited toxicity on the abundance of, and processes driven by, microorganisms in freshwater or estuarine biofilms, 15,[36][37][38][39] except at concentrations (1000 μg l −1 ) far higher than modelled environmental concentrations (1-100 ng l −1 ). [40][41][42] Shifts in species composition of bacterial communities have been recorded at Ag-NP concentrations of 200 μg l −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Shifts in species composition of bacterial communities have been recorded at Ag-NP concentrations of 200 μg l −1 . 36,39,43,44 The link between alteration of community composition by NPs and modification of associated processes is not straightforward; for instance, bacterial activity to degrade hydrocarbons can be maintained in presence of Ag-NPs, despite significant modification of the composition of the bacterial communities. 36 Toxicity of NPs to microorganisms has also been shown to be taxon specific, 37 and influenced by environmental parameters, such as presence of UV light for TiO 2 -NPs 2 and Ag-NPs, 45 and temperature for Ag-NPs.…”
Section: Introductionmentioning
confidence: 99%